Improvement of T1 lipase of Geobacillus zalihae by directed evolution - Abdul Rachman, Abdul Rahim (2014)
Directed evolution is one of the methods to improve the characteristic of an enzyme such as activity, optimum temperature, pH, stability, substrate specificity and enantioselectivity. Directed evolution relies on random mutation and high throughput screening. This study is mainly conducted to improve the characteristic of native recombinant T1 lipase by directed evolution by using two methods in directed evolution which are DNA shuffling and error prone polymerase chain reaction (PCR) to create potential mutant for further studies. No reported so far about improvement of T1 lipase by using directed evolution method. In addition, lack understanding on the factor affecting specific activity and other characteristic of T1 lipase became the reason why this method was chosen. UPM-1 lipase and T1 lipase gene were digested randomly by using Dnase I and reassambled together before error prone PCR were taken place. Reassambled products were amplified using specific primers of T1 lipase. Full length of mutated gene was cloned into pTrHis TOPO TA expression vector and transformed into Escherichia coli TOP 10 host. More than 1500 colonies, only eleven transformants gave rise to clearing zone on trybutyrin agar plate. Eleven putative colonies were proceed for preliminary lipase activity to screen the best among eleven colonies. Only M1 and M3 chimeric lipases with lipase activity above 5 U/ml were subjected to further study. M1 and M3 chimeric lipases were purified with 1.48 fold and 2.36 fold higher specific lipase activity than native T1 lipase, respectively. Random mutations on M3 chimeric lipase increased the optimum temperature from 65°C to 70°C, but the optimum pH was shifted from pH 9 to pH 8 as compared to native T1 lipase. About 194 mutations on M1 chimeric lipase significantly decreased the optimum temperature from 65°C to 55°C but had high lipase activity at pH 6 until 9 with wide pH range compared to native T1 lipase.Interestingly, M1 chimeric lipase has twenty percent lipase activity at pH 4 and pH 5 while no sign of lipase adetected. Substrate specificity for both mutants was not changed as compared to native T1 lipase whereby long carbon chain length substrates were preferable. Improvement of lipase activity for both chimeric lipase (M1 chimeric and M3 chimeric) were closely related with distance of serine-histidine-aspartic acid catalytic center. Distance between histidine and serine were shorten from 3.5Å (native T1) into 3.2Å (M1 chimeric) and 3.0Å (M3 chimeric). Proline addition at position 87 in M3 chimeric protein sequence became main reason why distance of serine-histidine catalytic center for M3 chimeric lipase was shortened. M1 chimeric lipase protein structure showed 194 mutations at Nterminal and C-terminal in protein sequence without change three amino acid catalytic center (serine-aspartic-histidine). Combination of mutation make M1 chimeric lipase characteristic such as optimum temperature, protein stability and pH profile were altered compared to native T1 lipase. As conclusion, directed evolution as been successfully altered and improved characteristic of T1 lipase such as optimum temperature, enzyme stability and pH profile.